Nursing Management for Prevention of Transition Seasonal Diseases, Socialization of My Medicine Application and Medication in the Foster Village of Karang Jompo, Tirto District, Pekalongan Regency - Irnawati Irnawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Health education about nursing management for prevention of transition seasonal disease, socialization of My Medicine application and medication activities have a purpose to make the community in the foster village of Karang Jompo have proficiency in: (1) increase knowledge about nursing management for prevention of transition seasonal disease, socialization of My Medicine application; (2) increase awareness of the disease; (3) increase awareness for treatment to health service. The target audience of these activities are community in the foster village of Karang Jompo, Tirto District, Pekalongan Regency. Implementation of activities carried out by health education about s nursing management for prevention of transition seasonal disease, socialization of My Medicine application, medication, and blood test. The results of this community service activity are that the average respondent is 51 years old, most of them are female, and most of them have primary education, 20% complain of dizziness, most of the residents when they are sick 46% go to community health centers, most of them are 81% know how to prevent Dengue Hemorrhagic Fever, 71% know how to prevent transitional season diseases. It is hoped that the community can apply the knowledge gained in everyday life to avoid disease in the transition season.